Does a promise script work to reduce the hypothetical bias? Evidence from an induced value experiment - Botao Qin (Kiel Institute for the World Economy (IfW), 2019)
This paper explores whether a truth-telling promise can work to reduce the hypothetical bias in preference elicitation. Using an induced value experiment in China with a random nthprice auction, the author finds: 1) Hypothetical bias exists in a random nth-price auction with induced values and making a truth-telling promise can reduce the hypothetical bias. 2) All treatments are demand-revealing except for the hypothetical baseline.
http://dx.doi.org/10.7910/DVN/L5CTMC
Keywords: C90; D44; Q51; 330; hypothetical bias; oath; random nth-price auction; induced value experiment